Acute fatty liver of pregnancy associated with severe acute pancreatitis: a case report - Oliveira, Cássio Vieira de [UNESP]; Moreira, Alecsandro [UNESP]; Baima, Julio P. [UNESP]; Franzoni, Leticia de C. [UNESP]; Lima, Talles B. [UNESP]; Yamashiro, Fabio da S. [UNESP]; Coelho, Kunie Yabuki Rabelo [UNESP]; Sassaki, Ligia Y. [UNESP]; Caramori, Carlos Antonio [UNESP]; Romeiro, Fernando G. [UNESP]; Silva, Giovanni F. [UNESP] (Baishideng Publishing Group Inc, 2014)
Acute fatty liver of pregnancy is a rare disease that affects women in the third trimester of pregnancy. Although infrequent, the disease can cause maternal mortality. The diagnosis is not always clear until the pregnancy is terminated, and significant complications, such as acute pancreatitis, can occur. Pancreatic involvement typically only occurs in severe cases after the development of hepatic and renal impairment. To date, little knowledge is available regarding how the disease causes pancreatitis. Treatment involves supportive measures and pregnancy interruption. In this report, we describe a case of a previously healthy 26-year-old woman at a gestational age of 27 wk and 6 d who was admitted with severe abdominal pain and vomiting. This case illustrates the clinical and laboratory overlap between acute fatty liver of pregnancy and pancreatitis, highlighting the difficulties in differentiating each disease. Furthermore, the hypothesis for this overlapping is presented, and the therapeutic options are discussed.
Keywords: Acute fatty liver of pregnancy; Fulminant hepatic failure; Liver disease in pregnancy; Severe acute pancreatitis